A novel biomass thermoresponsive konjac glucomannan composite gel developed to control the coal spontaneous combustion: Fire prevention and extinguishing properties. (15th December 2021) - Wang, Liang; Liu, Zhongyong; Yang, Hongyu; Li, Haitao; Yu, Minggao; He, Tao; Luo, Zhongzheng; Liu, Feng
Highlights: A novel biomass thermoresponsive composite gel was facilely synthesized. The gel has a controllable gelation time and good water retention ability. The gel showed good inhibition effect and excellent fire extinguishing performance. Abstract: Spontaneous combustion in coal mines continues to pose a significant risk. A novel biomass composite thermoresponsive gel produced by mixing konjac glucomannan (KGM) with fly ash (FA) was prepared to prevent coal spontaneous combustion. The composite gel had a controllable gelation time, a good seepage capacity, a high water retention capacity, a good combustion inhibition effect and an excellent fire extinguishing effect. Scanning electron microscopy indicated that the FA strongly interfacially adhered to the three-dimensional KGM framework and the gel wrapped around the coal surfaces well. Energy dispersive X-ray spectroscopy element mapping indicated that the FA was mixed uniformly with the KGM gel. The KGM@FA gel oxidation characteristics were analyzed by thermogravimetry infrared analysis and low-temperature coal oxidation system. The KGM@FA gel was found to effectively inhibit coal temperature increases, heat accumulation and CO generation during the process of oxidation and combustion, which would decrease the likelihood of coal spontaneous combustion. Fire-extinguishing experiments indicated that the gel covered the surfaces of burning coal well and markedly decreased the fire temperature and CO emissions and therefore stably extinguished the fire without combustion restarting. The KGM@FA gel is therefore an effective fire prevention and extinction material.